Estudo murinométrico, histológico e imuno-histoquímico da influência da obesidade no desenvolvimento da osteonecrose experimental induzida por bifosfonato - Lima, Wilson José de Miranda (2023)
Osteonecrosis is a disease characterized by the death of bone constituents. Some compounds, such as bisphosphonates, which work by inhibiting bone resorption, can induce osteonecrosis. When the disease occurs in the jaws induced by the use of bisphosphonates, it is called BRONJ - Bisphosphonate Related Osteonecrosis of the Jaws. Obesity is considered a public health problem and is related to other oral diseases, such as caries and periodontal disease. This study is pioneering in identifying the relationship between obesity and bisphosphonate-induced osteonecrosis. The aim of this work was to analyze the influence of obesity on the development of bisphosphonate-induced osteonecrosis through murinometric, histological, immunohistochemical, and morphometric analyses. The experiment consisted of 24 male Wistar rats (Rattus norvegicus) with an approximate age and weight of 30 days and 180g. They were randomly and simply divided into four groups: healthy, osteonecrosis, obese, and obese with osteonecrosis. Osteonecrosis was induced using zoledronic acid in an injectable solution of 4mg/5mL via intraperitoneal, at a dose of 250μg/Kg, once a week for eight weeks, along with bone trauma (extraction of the left lower first molar) and induction of obesity using a high-glycemic-index diet. Each group was qualitatively and quantitatively evaluated for obesity development, osteonecrosis development, as well as macroscopic and microscopic maxillary lesions. The results were expressed as the mean percentage and standard deviation and statistically analyzed using one-way analysis of variance (ANOVA) followed by Tukey's post-test (α = 5%). The obese and obese with osteonecrosis groups showed higher means and standard deviations for the following obesity evaluation parameters: weight gain (350.6 ± 92.19 g and 341.9 ± 91.43 g, respectively), nasoanal length (27.17 ± 1.16 cm), Lee index (0.30 ± 0.00 g/cm), body mass index (0.68 ± 0.04 g/cm² and 0.69 ± 0.04 g/cm²), and abdominal circumference (20.5 ± 0.21 cm and 19.1 ± 0.14 cm). The obese group also had a larger chest circumference (18.0 ± 1.28 cm), as well as a higher adiposity index in animals receiving the high-glycemic-index diet (obese group - 10.0 ± 1.03 g and obese with osteonecrosis group - 10.4 ± 0.86 g). Morphologically, it was observed that animals in the osteonecrosis group and obese with osteonecrosis group had larger areas of necrosis (means: 172.83 ± 18.19 μm² and 290.33 ± 15.77 μm², respectively) (p < 0.0001). Hepatic steatosis and increased adipocyte size were observed in the obese group (mean: 97.75 ± 1.91 μm²) and the obese with osteonecrosis group (mean: 98.41 ± 1.56 μm²), indicating greater tissue damage in these groups (p < 0.0001). Regarding immunohistochemical analyses, the healthy and obese groups showed intense extracellular matrix deposition. For TNF-alpha, intense and multifocal staining was observed in the osteonecrosis (27.59 ± 7.65 μm²) and obese (25.52 ± 8.31 μm²) groups. For TGF-β, staining was also intense and multifocal, especially in the obese with osteonecrosis group (44.98 ± 3.93 μm²). As for collagen I, staining was more intense in healthy animals (26.73 ± 8.29 μm²), while in other groups, it was discrete and focal. The influence of obesity on the development of osteonecrosis is evident, as animals in the obese and obese with osteonecrosis groups demonstrated greater tissue damage. The study suggests that TNF-alpha and TGF-β may play important roles in bone tissue damage and repair. The potential interaction between TGF-β, TNF-alpha, and collagen I in bone tissue could be essential for understanding bone remodeling, disease prevention, and treatment. Therefore, further studies are needed to explore the existing mechanisms.